Sie sind auf Seite 1von 7

Classical Mechanics - Homework Assignment 4

Alejandro G´omez Espinosa October 18, 2012

Goldstein, Ch.3, 18 At perigee of an elliptic gravitational orbit a particle experiences an impulse S in the radial direction, sending the particle intro another elliptic orbit. Determine the new semimajor axis, eccentricity, and orientation in terms of the old.

axis, eccentricity, and orientation in terms of the old. Figure 1: Sketch of a particle moving

Figure 1: Sketch of a particle moving in an elliptic gravitational orbit experience an impulse S in the perigee.

This exercise is described in the Figure 1. Here, in the perigee the particle experiences an impulse S, then:

S = ∆p = p f p i

p f = p i + S r

where p i is perpendicular to r and S is in the direction of r . To determine the new semimayor axis and the eccentricity, we must calculate first the angular momentum (l) and the energy (E):

l f = r × p f = r × (p i + S r ) = r × p i + 0 = l i

This means that ∆l = 0, that makes sense since ∆p is in the radial direction. In the case of the energy after the impulse:

r˙ f = f ·

= p f

m

r

E f =

1

2 µr˙

2

f

· r = p i + S r

m

· r = S

m

=

µS 2

2m 2

=

µm

S 2

2m

since p i is perpendicular to r. Now, the eccentricity is:

e f 2 = 1 + 2El mk 2 2

2

= 1 + mk 2l 2 (E i + E f ) = e

2

i

gomez@physics.rutgers.edu

1

+ 2E

mk 2

f

l

2
i mk 2

= e

2

i

+ lS

where, in the case of a graviational potential, k = GmM . Then, the new semimayor axis is:

a =

l

1

mk (1 e 2 )

the new semimayor in terms of the initial one must be:

a

f

a

i

2

i

= 1 e

1 e 2

f

=

1 e

2

i

1 e

2

i

l 2 S 2 m 2 k 2

=

1

1 l 2 S 2

m 2 k 2

1

(1e

2

i

)

a f =

a i

1 a i S 2

mk

=

1

1 a i S 2

mk

Finally, for the orientation, let’s write the initial orbit as:

and the final as:

r i (φ) =

l

2

1

mk 1 e i cos φ

r f (φ) =

l

2

1

mk 1 e f cos(φ + φ 0 )

in the perigee, both orbits must be equal and φ = π:

r i (φ = π)

=

r f (φ = π)

1 1

=

1 + e i

+ e i

cos φ

1

1 1 + e f cos(φ 0 ) e i

+ e f cos(φ 0 )

=

=

e f

Goldstein, Ch.3, 29 If all the momentum vectors of a particle along its trajectory are translated so as to start from the center of force, then the heads of the vectors trace out the particle’s hodograph, a locus curve of considerable antiquity in the history of mechanics, with something of a revival in connection with space vehicle dynamics. By taking the cross product of L with the Laplace-Runge-Lenz vector A. Show that the hodograph for elliptical Kepler motion is a circle of radius mk/l with origin on the y axis displaced a distance A/l from the center of force.

The Laplace-Runge-Lenz vector is given by:

A = p × L mkr

r

where p is the momentum of the particle of mass m in a central force potential. Define the unit vector

r

r

= cos θ x + sin θ y

In addition, we know that the angular momentum vector is in the z direction: L = lz , thus:

A

= p × L mk (cos θx + sin θy )

= l(p × z ) mk cos θx mk sin θy

2

Taking the cross product:

L × A = l 2 z × (p × z ) mkl cos θy + mkl sin θx

here, taking p = p x x + p y y , the product:

z × (p × z ) = z × (p x y + p y x

) = p x x + p y y = p

then:

L × A = l 2 p mkl cos θy + mkl sin θx

Now, from equation (3.86) of Goldstein, we know that the value of the Laplace- Runge-Lenz vector in the perihelion is A = mkex , where e is the eccentricity. If we start the hodograph in the perihelion, we can match:

L × (mkex )

=

mkely

=

mkey

=

p

=

p

=

l 2 p mkl cos θy + mkl sin θx

l 2 p mkl cos θy + mkl sin θx

lp mk cos θy + mk sin θx

mk

l

mk

l

sin θx + mke

l

+ mk

l

cos θ y

sin θx + A

l

+ mk

l

cos θ y ⇐⇒ A = mke

where we can confirm that r = mk/l and the center is in the origin, displaced in the direction of y a distance A/l.

Goldstein, Ch.3, 31 Examine the scattering produced by a repulsive central force f = kr 3 . Show that the differential cross section is given by

k

(1 x)dx

σ(Θ)dΘ =

2E x 2 (2 x) 2 sin πx

where x is the ratio of Θand E is the energy.

Starting with the differential equation of the orbit:

d 2 u dθ 2

+ u = m l 2 du V u

d

1

where u = 1/r . We must express the repulsive central force in terms of a potential V (1/u):

f = −∇V

then, the orbit equation is:

d 2 u

2

+ u = m ku

l

2

that has the solutions when α 2 = 1 + mk :

l

2

V =

k 2 = ku 2

2r

2

d 2 u + 1 + mk u = 0

2

l

2

u = A cos(αθ) + B sin(αθ)

3

Then, let’s use boundary conditions. In the case where r → −∞, i.e., the particle is moving in the direction of the potential but is very far away, the variable u 0 and the angle θ = π:

u(θ = π)

=

0

A cos(απ) + B sin(απ)

=

0

A

=

B tan(απ)

(1)

On the other hand, once the particle experienced scattering, it moves in an angle

θ = Θ when r → ∞, then

u 0:

u(θ = Θ)

=

0

A cos(αΘ) + B sin(αΘ)

=

0

(2)

Replacing (1) in (2):

B tan(απ) cos(αΘ) + B sin(αΘ)

=

0

B(sin(αΘ) tan(απ) cos(αΘ))

=

0

sin(αΘ) tan(απ) cos(αΘ)

=

0

cos(απ) sin(αΘ) sin(απ) cos(αΘ)

=

0

sin(αΘ απ)

=

0

απ)

=

π

α(x 1)

=

1

⇐⇒

x = Θ

 

π

 

1

α

=

x 1

Replacing α in the expression above:

α

2

=

x 1 2

1

=

1 + mk

l

2

1 + mk

l

2

In terms of the impact parameter s, l = mv 0 s = s 2mE. Thus,

1 k

=

(x 1) 2

1 +

2Es 2

k 1 (x 1) 2

2Es 2

1 2

s

=

=

s 2 =

(x 1) 2

2E

x(2 x)

1) 2

k

(x

2

2E x(2 x)

k

(x

1)

Derivating both sides:

2sds =

k

2(x 1)

2) 2 dx = k

(1 x)

E x 2 (2 x) 2 dx

2E x 2 (x

4

Finally, the differential cross section is:

σ(Θ)dΩ =

|sds|

sin Θ =

k

(1 x)

2E x 2 (2 x) 2 sin() dx

Goldstein, Ch.3, 35 Another version of the truncated Coulomb potential has the form

V

V

k k a

r

=

= 0

r < a r > a

Obtain closed-form expressions for the scattering angle and the differential scatter- ing cross section. These are most conveniently expressed in terms of a parameter

What is the total cross

measuring the distance of closest approach in units of a. section?.

the distance of closest approach in units of a. section?. Figure 2: Sketch of the problem

Figure 2: Sketch of the problem 35. Here, θ is the angle

xob, γ =

.

φ = doc = cob and Θ = xoe

xod, ξ =

aob =

eod,

We have two cases, consider the case where the potential vanishes:

where

1

2

mr˙ 2 + 1

2 mr 2 θ 2

˙

1

2

mr˙ 2 +

l 2

2mr 2

dr

dt

˙

mr 2 θ

dt

5

=

=

=

=

=

E

E

m E

2

2

2mr 2

l

l

l

mr 2

(3)

(4)

Dividing (3) by (4):

dr

m E

2

2mr 2

l

2

=

 

l

 

mr 2

 
 

1

dr

=

 

r 2

2Em

l

2

1

r 2

Replacing α

thus,

0 2 = 2Em

l

2

and making the change in the variable:

u = 1 r

du = d 1

r = 1 2 dr

r

=

du

α 0 u 2

2

changing the variable one more time:

then,

u = α 0 cos x

du = α 0 sin xdx

α 0 sin xdx α 1 cos 2

x =

dx =

x = θ θ 0

where we can take θ 0 = π/2 just to have our coordinates in the regular form. Going back to our original variable:

1 r = u = α 0 cos x = 2Rm cos(θ π )

l

2

2

1

r = 2Rm

l

2

cos(θ π )

2

For the second part of the exercise, when r < a:

1

2 mr˙ 2 +

l

2

2mr 2 + k

r

k

a

1

2 mr˙ 2 +

2

2mr 2 k

l

r

=

=

 

(5)

E

E

(6)

where k = k and E = E+ k a . Equation (5) is the regular central potential equation, where the solution, in terms of the angles described in Figure 2 are:

1

r = β 1 + 1 +

2 cos γ π β = k m ,

α

β

2

l

2

α = 2E m

l

2

(7)

here, according with the angles introduced in Figure 2, the angle γ = Θ + ξ. Then, (6) and (7) must be equal when the particle start experiencing the potential:

2Em

l

2

cos θ π = β 1 + 1 +

2

α

β

2

6

cos γ π

2

(8)

Then, from the Figure 2, we can see that γ = Θ + ξ therefore:

cos γ π = cos Θ + ξ π = sin (Θ + ξ) = sin Θ cos ξ + cos Θ sin ξ

2

2

= a 2 s 2

a

s

sin Θ + a cos Θ

(9)

For the angle θ, we can probe that ξ = π θ, thus:

cos θ π = cos π ξ π = sin ξ =

2

2

s

a

(10)

Replacing (9) and (10) in (8) and, the values of β and α:

2Em

s

a

l

2

2Em

s

a

l

2

sl 2Em

a

=

=

=

β 1 + 1 +

α 2 a 2 s 2
β

a

sin Θ + a cos Θ

s

k m + k 2 m 2 + 2E ml 2 a 2 s 2

l

2

l

2

a

sin Θ + a cos Θ

s

k m + k 2 m 2 + 2E ml 2 a 2 s 2 sin Θ + a cos Θ

2 √ a 2 − s 2 sin Θ + a cos Θ a s (11)

a

s

(11)

where we have a function s(Θ). Once we derivate both sides, we will found an expression for s ds that we can replace in:

σ(Θ)dΩ = sin |sds| Θ

to find the differential cross section and for the total cross section, we have to derivate in the solid angle dΩ.

7